Jurnal Pendidikan IPA Indonesia - W. Sumarni (Prodi IPA Fak. MIPA UNNES dan PPII, 2016)
- Project Based Learning (PBL) to Improve Psychomotoric Skills : A Classroom Action Research - Socio Scientific Issues (SSI) in Reaction Rates Topic And Its Effect on The Critical Thinking Skills of High School Students - The Development of Laboratory-Based Earth and Space Science Learning Model to Improve Science Generic Skills of Pre-Service Teachers - The Influence of Science Learning Set Using Scientific Approach and Problem Solving Model on Learning Outcomes of Junior High School Students in The Subject of Heat And Temperature - Analysis of Mental Model of Students Using Isomorphic Problems in Dynamics of Rotational Motion Topic - The Development of Audio-Visual Student Portfolios (LKS) Contextual Teaching and Learning-Based )CTL) on Sound Chapter of Science Subject for Deaf Students - Student Argumentation in Science Lessons : A Story of Two Research Projects - The Effectiveness Using Inquiry Based Natural Science Module With Authentic Assessment to Improve The Critical Thinking And Inquiry Skills of Junior High School Students